2022
DOI: 10.1007/s12144-022-03301-w
|View full text |Cite
|
Sign up to set email alerts
|

What exists in academia on work stress in accounting professionals: a bibliometric analysis

Abstract: This study aims to fill a gap in the literature by conducting the scientific and bibliometric mapping of work stress in accounting professionals, using a methodological trilogy that contributes to this topic, namely the application of the ROC curve, Prisma and R bibliometric tools. Through the analysis of a sample of 103 articles, it was found that, in order to avoid and/or overcome the levels of stress in accountants, the following factors should be taken into account: (1) a high engagement with work, (2) red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 122 publications
0
0
0
Order By: Relevance
“…The bibliometrics research follows a mixed methodology, as it provides an assessment of the qualitative and quantitative scope of each research subject which allows mapping a large volume of information contained in databases (Pritchard 1969). The bibliometrics is extremely useful for identifying the publication trends in topics/emergence terms and become dominant and influential in defining future research (Rodrigues et al 2022).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The bibliometrics research follows a mixed methodology, as it provides an assessment of the qualitative and quantitative scope of each research subject which allows mapping a large volume of information contained in databases (Pritchard 1969). The bibliometrics is extremely useful for identifying the publication trends in topics/emergence terms and become dominant and influential in defining future research (Rodrigues et al 2022).…”
Section: Methodsmentioning
confidence: 99%
“…This study will use this bibliometric database's quantitative and qualitative approach. Some authors have developed bibliometric studies of the associated concepts at the level of scientific papers published in a particular journal (Rodrigues et al 2022;Bandara et al 2011;Briner and Denyer 2012), or the analysis of research in a specific country (Weerasinghe 2017;Geissdoerfer et al 2017).…”
Section: Methodsmentioning
confidence: 99%
“…students find this tool attractive because it helps them in the process of developing academic work. Numerous research has already been conducted on this subject, that have concluded the plagiarism issues in using generative AI tools (Rodrigues et al, 2024) [24] . The researchers also assess the experiences of the respondents if their utilization of AI made them more interested in the lessons of the teacher.…”
Section: Moderatementioning
confidence: 99%
“…In contemporary times, bibliometric analysis has gained significant traction within the realm of business research (Donthu et al, 2020;Donthu et al, 2021;Khan et al, 2021). Previously, research has taken place on understanding the academic patterns and aspects of occupational stress through bibliometric review (Rodrigues et al, 2022;Sidhu et al, 2020;Zhang et al, 2021) in various sectors such as healthcare (Costin et al, 2023) and finance (Rodrigues et al, 2022). Georgi et al, (2017) conducted a systematic literature review to examine the factors contributing to work-related stress by adhering to the principles set by the "Meta-analyses of Observational Studies in Epidemiology" (MOOSE) group and included a review of 20 papers; the authors of these respective papers have investigated various parameters to assess the work-related stress in banks.…”
Section: Introductionmentioning
confidence: 99%